Comparison of the expression and toxicity of AAV2/9 carrying the human A53T α-synuclein gene in presence or absence of WPRE. Issue 2 (February 2021) - Sun, Xiuping; Yu, Xuan; Zhang, Ling; Zhao, Wenjie; Wang, Manshi; Zhang, Yu; Li, Xianglei; Gao, Ran; Breger, Ludivine S.; Dovero, Sandra; Porras, Gregory; Fernagut, Pierre-Olivier; et al.
Abstract: Woodchuck Hepatitis Virus Post-transcriptional Regulatory Element (WPRE) is thought to enhance transgene expression of target genes delivered by adeno-associated viral (AAV) vectors. This study assessed the protein expression of α-synuclein, phosphorylated α-synuclein at Serine 129, extent of nigrostriatal degeneration as well as subsequent behavioral deficits induced by unilateral intranigral stereotactic injection in male adult C57BL/6J mice of an AAV2/9 expressing A53T human α-synuclein under the control of the synapsin promoter in presence or absence of the WPRE. The presence of WPRE enabled to achieve greater nigrostriatal degeneration and synucleinopathy which was concomitant with worsened forelimb use asymmetry. This work refines a mouse Parkinson's disease model in which anatomo-pathology is related to behavioral deficits. Abstract : Parkinson's disease; Synucleinopathy; Woodchuck hepatitis virus post-transcriptional regulatory element; Mouse.